Role of the settlement network in the formation of territorial communities in the Kolomyia district of the Ivano-Frankivsk oblast - Ivan Kostashchuk; Yurii Bilous; Bohdan Verbishchuk (Kazimierz Wielki University, 2022)
This article examines the peculiarities of the settlement network of the established Kolomyia district (raion) of Ivano-Frankivsk oblast and its importance in the formation of territorial communities (hromada). We analyzed the peculiarities of the functioning of local settlement systems through the indicators of transport accessibility to the center of the community and administrative service centers, as well as the concentration coefficient of the population. We identified strengths and weaknesses, as well as threats and opportunities during the SWOT-analysis.